Pengaruh Perbandingan Puree Biji Buah Nangka (Artocarpus Heterophyllus) Dengan Tepung Terigu Pada Pembuatan Kulit Pie Terhadap Daya Terima Konsumen - Gita Adelia; Mutiara Dahlia; Sachriani Sachriani (Syntax Idea)
This plant has different names and varies depending on the region or region. Jackfruit plant is a plant that belongs to the annual fruit type, and is still related to Malvales and is also included in the ordoUrticales. This study was conducted to find out how the comparison of jackfruit seed pulp (Artocarpus heterophyllus) with wheat flour on pie peel making on consumer acceptability. The research was conducted starting in March 2021 at the Bakery and Bakery Laboratory, Faculty of Engineering, State University of Jakarta. This study used experimental methods. Consumer acceptance tests were conducted on 30 untrained panelists to rate pie crusts for interior color, subtle flavor, buttery flavor, subtle flavor, sweetness, and texture. The results of consumer acceptance obtained by Friedman's test showed that there was no noticeable difference in sweetness, but there was a noticeable difference in the intense color, mash flavor, butter flavor, mash flavor and texture. Then continued with the Tuckey test with a significance value of Î± = 0.05 and showed that pie skin has a noticeable difference of 10%, 20-30% and a tendency to like pie skin compared to pure jackfruit seeds by 20%. Therefore the recommended treatment in this study was oilcake peel and compared to jackfruit seed puree 20%. The conclusion is that comparing jackfruit seed puree does not affect consumer acceptance of the sweet taste of pie peel.